Computational Modeling of Transient Processes During Run-In for Tribological Systems - (:unkn) unknown (My University, 2016)
Understanding the frictional behavior of machine elements in mutual rolling or sliding contact is important for many engineering applications. When frictional sliding is initiated, the tribological system passes through several stages with each stage possessing its own unique frictional property. The initial transition process preceding stationary sliding is usually called “run-in”. During the run-in time interval, surface topographies of frictional contacts as well as lubricant distribution and surface tribofilms reorganize and adjust through asperity deformation and wear processes before reaching the steady state. This surface stability formed during run-in leads to an improvement in frictional performance during steady state operation, which increases equipment life and efficiency. Thus, understanding of the frictional transient process and optimizing the time schedule required for the run-in of equipment such as for aircraft engines and naval vessel gas turbines can lead to improved solutions for more desirable operating conditions for the lifetime of the equipment. This thesis investigates the running-in of both lubricated and unlubricated frictional contact in order to gain insight into how friction changes during this time interval. For lubricated friction, it is shown that the surface topography and lubricating fluid goes through a self-organization process during run-in caused by frictional mechanisms that change the surface topography and removes fluid from the area of contact until friction and wear at the interface reaches its equilibrium value. For unlubricated friction, three common tribo-mechanical systems undergoing dry sliding during run-in are investigated: the pin-on-disk, a journal bearing, and a piston-cylinder system. Using computer simulation, a transient frictional response curve is presented for various frictional conditions in order to gain insight into how the frictional value changes during run-in. It is shown that adjustment of the static coefficient of friction can dramatically affect the response behavior with higher coefficient of friction values resulting in higher frictional forces and longer times to reach equilibrium, while smaller values shorten time to equilibrium and reduce frictional forces. These discoveries suggest seeking ways to optimize the materials in order to optimize the transient friction during run-in which are summarized in the conclusion.
Keywords: Friction; Self-Organization; Tribology; Wear